2022
DOI: 10.1126/science.abm8566
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic-functionalized interfaces for highly efficient inverted perovskite solar cells

Abstract: Further enhancing the performance and stability of inverted perovskite solar cells (PSCs) is crucial for their commercialization. We report that the functionalization of multication and halide perovskite interfaces with an organometallic compound, ferrocenyl-bis-thiophene-2-carboxylate (FcTc 2 ), simultaneously enhanced the efficiency and stability of inverted PSCs. The resultant devices achieved a power conversion efficiency of 25.0% and maintained >98% of their initial efficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
668
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 718 publications
(678 citation statements)
references
References 44 publications
10
668
0
Order By: Relevance
“…[1][2][3][4] At present, the state-of-the-art traditional (n-i-p) PSCs have a reached record PCE of 25.7%. [5] Inverted PSCs have made great breakthroughs, [6] but their PCE are still behind the traditional PSCs. The inverted PSCs display less hysteresis effect, better stability, and excellent compatibility with tandem cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] At present, the state-of-the-art traditional (n-i-p) PSCs have a reached record PCE of 25.7%. [5] Inverted PSCs have made great breakthroughs, [6] but their PCE are still behind the traditional PSCs. The inverted PSCs display less hysteresis effect, better stability, and excellent compatibility with tandem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Long and their colleagues have developed a novel organometallic compound, ferrocenyl-bis-thiophene-2-carboxylate (FcTc2), as an interface layer to enhance the efficiency and stability of inverted PSCs as shown in Fig. 2 [17]. The FcTc2 functionalized devices obtained a champion power conversion efficiency (PCE) of up to 25.0% (with certified 24.3%), which is the record efficiency for inverted PSCs.…”
mentioning
confidence: 99%
“…State-of-art PSCs are nowadays fabricated by using a 2D perovskite layer on top of a bulk (3D) perovskite absorber. [176] Such 3D/2D heterostructures strategy is not limited to PSCs, in fact an NREL team has recently demonstrated that this is a general concept that can be efficiently considered for several thin film PV such as CdTe and CIGS. [177] Figure 9.…”
Section: Perspectives On Future Materials For Space Pvmentioning
confidence: 99%